A Review of Methods to Modify the PDMS Surface Wettability and Their Applications - Neves, Lucas Boniatti (2024)
Polydimethylsiloxane (PDMS) has attracted great attention in various fields due to its excellent properties, but its inherent hydrophobicity presents challenges in many applications that require controlled wettability. The purpose of this review is to provide a comprehensive overview of some key strategies for modifying the wettability of PDMS surfaces by providing the main traditional methods for this modification and the results of altering the contact angle and other characteristics associated with this property. Four main technologies are discussed, namely, oxygen plasma treatment, surfactant addition, UV-ozone treatment, and the incorporation of nanomaterials, as these traditional methods are commonly selected due to the greater availability of information, their lower complexity compared to the new techniques, and the lower cost associated with them. Oxygen plasma treatment is a widely used method for improving the hydrophilicity of PDMS surfaces by introducing polar functional groups through oxidation reactions. The addition of surfactants provides a versatile method for altering the wettability of PDMS, where the selection and concentration of the surfactant play an important role in achieving the desired surface properties. UV-ozone treatment is an effective method for increasing the surface energy of PDMS, inducing oxidation, and generating hydrophilic functional groups. Furthermore, the incorporation of nanomaterials into PDMS matrices represents a promising route for modifying wettability, providing adjustable surface properties through controlled dispersion and interfacial interactions. The synergistic effect of nanomaterials, such as nanoparticles and nanotubes, helps to improve wetting behaviour and surface energy. The present review discusses recent advances of each technique and highlights their underlying mechanisms, advantages, and limitations. Additionally, promising trends and future prospects for surface modification of PDMS are discussed, and the importance of tailoring wettability for applications ranging from microfluidics to biomedical devices is highlighted. Traditional methods are often chosen to modify the wettability of the PDMS surface because they have more information available in the literature, are less complex than new techniques, and are also less expensive.